Prediction of duration of labor based on biomechanical measurements of the cervix: A preliminary study. (January 2020) - Salaets, Eline; Richter, Jute
Abstract: Objective: Induction of labor is a common procedure in obstetrics. Predictability of duration of labor could facilitate planning as well as patient's satisfaction. The primary purpose of this study was to evaluate the usefulness of a new biomechanical measurement of the cervix based on the aspiration technique for predicting the duration of labor after induction. Study design: This was a prospective single centre study. Inclusion criteria were term nulliparous pregnant women with an unfavourable cervix who needed an induction of labor. Digital (Bishop score), sonographic (cervical length and cervical consistency index (CCI)) as well as aspiration measurements (closure pressure) of the cervix were performed and compared to duration of labor. The technical feasibility and the acceptability of the measurements were explored. Results: There were no technical complications of the sonographic or aspiration measurements. Measuring the Bishop score was reported as most painful examination. Both the time to active phase of labor and the time to delivery is significantly correlated with the Bishop score, but not with the cervical length, CCI or closure pressure. Conclusion: The new biomechanical measurement of the cervix, based on the aspiration technique, is technically feasible and acceptable. In our small cohort no correlation was found between the closure pressure and the duration of labor.